ANALISIS NILAI MANFAAT DALAM FENOMENA PEMBAGIAN TAKJIL GRATIS DI BULAN RAMADAN - Muhammad Wafi Hilman Luthfil Hadi; Jermanda Ridwan Kurniaji; Syamsul Hidayat (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
During the holy month of Ramadan, Indonesia experiences various unique cultural phenomena, one of which is the popular activity known as ngabuburit, or spending the late afternoon hours before breaking the fast. Common ngabuburit activities include reciting the Quran (tadarus) and hunting for takjil (light meals for breaking the fast). The tradition of sharing takjil has gained widespread attention across communities, symbolizing a spirit of generosity and sensitivity to social conditions, values that are deeply embedded in Islamic teachings. This study uses a qualitative research approach, integrating field data and literature review, to examine the social, economic, cultural, and educational impacts of takjil distribution during Ramadan. The research specifically considers the tradition's basis in hadith (Prophet Muhammad’s teachings) and its practical significance in Indonesian society. The findings highlight multiple benefits: economically, it supports local vendors and fosters financial circulation; socially, it enhances solidarity and strengthens community bonds; culturally, it preserves an important tradition; and educationally, it models charity and social responsibility for younger generations. Moreover, this practice fosters spiritual growth, as it is believed to increase faith, earn divine love from Allah and His Messenger, promote ukhuwah (brotherhood), purify intentions, and encourage mutual support and tolerance. By connecting religious values with social practices, the tradition of sharing takjil reinforces Indonesia’s collective identity and exemplifies the community's commitment to Islam’s principles of compassion and unity.